Baby massage dan sensory play meningkatkan motorik kasar bayi usia 6-12 bulan - Wiedyaningtyas, Chintya Kartika Putry; Yulianti, Atika; Rahmawati, Nurul Aini (Holistik Jurnal Kesehatan, 2025)
Background: During the golden age, various stimulations must be optimized, especially gross motor development. If the baby experiences gross motor delays, it can cause long-term effects, such as coordination disorders and decreased ability to adapt to the environment. Motor delays can occur due to several factors, including parenting patterns, maternal knowledge, health and nutritional status, environmental culture, and socio-economic status. Baby massage and sensory play are alternatives that can be used to stimulate infant growth and development. Purpose: To determine the effect of a combination of baby massage and sensory play on gross motor development in infants aged 6-12 months. Method: This study used a quasi-experimental design with a non-equivalent group design approach. The number of research samples was 30 infants aged 6-12 months who were taken using purposive sampling techniques according to the inclusion and exclusion criteria. The influence test used was the wilcoxon test for the experimental group and the paired sample t test for the control group, then both groups were compared using the Mann Whitney test. Results: The significance value for the intervention group was 0.010 (<0.05), indicating that the data were not normally distributed. The significance value for the control group was 0.006 (<0.05), indicating that the data were normally distributed. The criteria for assessing the effect of these significance values ​​indicate that the combination of infant massage and sensory play exercises has an effect on gross motor development in infants aged 6-12 months. The comparison test showed an Asymp. Sig. (2-tailed) of 0.690 (>0.05). The criteria for assessing the comparison test indicate that there is no comparison between the effect of the combination of infant massage and sensory play exercises on gross motor development in infants aged 6-12 months. Conclusion: The combination of infant massage and sensory play exercises has an effect on gross motor development in infants. Stimulation is necessary to optimize infants' gross motor skills; otherwise, their gross motor development will be delayed.                   Keywords: Baby; Baby Massage; Gross Motor; Sensory Play.   Pendahuluan: Pada masa golden age berbagai stimulasi harus dioptimalkan, terutama perkembangan motorik kasar. Apabila bayi mengalami keterlambatan motorik kasar, dapat menimbulkan efek jangka panjang, seperti gangguan koordinasi dan penurunan kemampuan adaptasi terhadap lingkungan. Keterlambatan motorik dapat terjadi karena beberapa faktor antara lain, pola asuh orang tua, pengetahuan ibu, status kesehatan dan gizi, budaya lingkungan, dan status sosial ekonomi. Baby massage dan sensory play merupakan salah satu alternatif yang dapat digunakan untuk menstimulasi tumbuh kembang bayi. Tujuan: Untuk mengetahui pengaruh kombinasi baby massage dan sensory play terhadap perkembangan motorik kasar pada bayi usia 6-12 bulan. Metode:  Penelitian ini menggunakan rancangan quasi experimental design dengan pendekatan non-equivalent group design. Jumlah sampel penelitian sebanyak 30 bayi berusia 6-12 bulan yang diambil menggunakan teknik purposive sampling sesuai dengan kriteria inklusi dan eksklusi. Uji pengaruh yang digunakan adalah uji wilcoxon untuk kelompok intervensi dan uji paired sample t test untuk kelompok kontrol, kemudian kedua kelompok dilakukan uji perbandingan menggunakan uji mann whitney. Hasil: Berdasarkan nilai signifikansi pada kelompok intervensi didapatkan sebesar 0.010 (< 0.05), berarti data tidak berdistribusi normal, sedangkan nilai signifikansi kelompok kontrol 0.006 (<0.05), berarti data berdistribusi normal. Kriteria penilaian uji pengaruh nilai signifikansi tersebut memiliki arti terdapat pengaruh kombinasi baby massage dengan sensory play terhadap perkembangan motorik kasar pada bayi usia 6-12 bulan. Pada uji perbandingan, menunjukkan Asymp. Sig. (2-tailed) sebesar 0.690 (>0.05). Kriteria penilaian uji perbandingan nilai signifikansi tersebut, memiliki arti tidak ada perbandingan pengaruh kombinasi baby massage dengan sensory play exercise terhadap perkembangan motorik kasar pada bayi usia 6-12 bulan. Simpulan: Ada pengaruh kombinasi baby massage dan sensory play terhadap perkembangan motorik kasar pada bayi. Pemberian stimulasi diperlukan untuk mengoptimalkan motorik kasar bayi, jika tidak perkembangan motorik kasar bayi akan mengalami keterlambatan.   Kata Kunci: Bayi; Baby Massage; Motorik Kasar; Sensory Play.